Blockade of Nuclear β‐Catenin Signaling via Direct Targeting of RanBP3 with NU2058 Induces Cell Senescence to Suppress Colorectal Tumorigenesis. Issue 34 (21st October 2022) - Zheng, Can‐Can; Liao, Long; Liu, Ya‐Ping; Yang, Yan‐Ming; He, Yan; Zhang, Guo‐Geng; Li, Shu‐Jun; Liu, Ting; Xu, Wen Wen; Li, Bin
Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors in the world, with high prevalence and low 5‐year survival. Most of the CRC patients show excessive activation of the Wnt/ β ‐catenin pathway which is a vital target for CRC treatment. Based on multiple CRC cell lines with different nuclear expression of β ‐catenin, NU2058 is identified from a small molecule library consisting of 280 bioactive compounds and found to selectively inhibit the proliferation of CRC cells with nuclear β ‐catenin activation in vitro and in vivo. The translational significance of NU2058 alone or in combination with chemotherapeutic drugs oxaliplatin and irinotecan (SN38) in CRC is demonstrated in orthotopic tumor model and patient‐derived xenograft models. By integrating limited proteolysis‐small molecule mapping (LiP‐SMap) and mass spectrometry (MS), Ran‐binding protein 3 (RanBP3) is identified as the direct target of NU2058. The results show that RanBP3 is a tumor suppressor in CRC and is associated with patient survival. Mechanistically, NU2058 increases the interaction of RanBP3 and β ‐catenin to promote nuclear export of β ‐catenin, which further inhibits transcription of c‐Myc and cyclin D1 to induce cell senescence. Collectively, NU2058 may serve as a promising therapeutic agent for CRC patients with selective disruption of pathologic Wnt/ β ‐catenin signaling. Abstract : Colorectal cancer (CRC) is one of the most common malignant tumors. Most of the CRC patients show excessive activation of Wnt/ β ‐catenin pathway which is a vital target for CRC treatment. Ran‐binding protein 3 (RanBP3) may be a promising prognostic biomarker and therapeutic target in CRC, and a preclinical rationale is provided for NU2058 as a potential strategy for cancer treatment.